Durian Marketing Strategy in Medan City: SWOT Analysis Approach, QSPM, CPM Method - Yuda Eka Danuarta; Desi Novita; M. Syarif Rafinda; Mhd. Ilahm Riyadh (CV. Media Digital Publikasi Indonesia, 2026)
The purpose of this study was to identify internal and external factors influencing the marketing strategies of two large local durian sellers in Medan City and to determine alternative local durian marketing strategies in Medan City using the Competitive Profile Matrix (CPM) method. This study employed quantitative analysis methods using SWOT analysis and Competitive Profile Matrix (CPM) analysis. The data sources used were primary and secondary data, with 10 sellers from each group. The sample for durian sellers and consumers was determined using purposive sampling. The results of this study indicate that the determining factors for durian marketing success are taste, packaging design, price, label completeness, packaging quality, sales location, and packaging color. The CPM analysis showed that Ucok Durian had the highest score, with a score of 2.8588. The strategies formulated for the sustainable competitiveness of the durian business are: 1) Emphasizing various product advantages, including strategic sales locations, constant stock availability, consistent taste, and maintaining permits and operational standards. 2) Innovating and improving the quality of durian souvenir packaging. 3) Pricing should be competitive with competitors.